2012
DOI: 10.1200/jco.2011.35.5198
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Clinical Trials of Off-Label Drugs Used to Treat Advanced-Stage Cancer

Abstract: The US Food and Drug Administration provides guidance to the pharmaceutical industry and others designing randomized clinical trials for regulatory approval. However, a gap exists for postregulatory decision makers, including patients, prescribers, and payers, because regulatory trials do not answer the questions most relevant to them. Therefore, guidance is needed for trials performed in the postapproval environment for these postapproval decision makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Clinical researchers have come to expect ''breakthrough efficacy'' as the hallmark of an agent effectively targeting a tumor driver. Indeed, revisions to clinical trial methodology to facilitate early approval of particularly active agents have been proposed by a number of groups, including patient advocacy organizations (Horning et al, 2013;Mullins et al, 2012). Moreover, the relatively recently acquired ability to collect wholegenome expression profiles and deep DNA sequence information from small amounts of tumor biopsy material has provided an opportunity to greatly expand the use of molecular profiling in guiding drug development and treatment decisions.…”
mentioning
confidence: 99%
“…Clinical researchers have come to expect ''breakthrough efficacy'' as the hallmark of an agent effectively targeting a tumor driver. Indeed, revisions to clinical trial methodology to facilitate early approval of particularly active agents have been proposed by a number of groups, including patient advocacy organizations (Horning et al, 2013;Mullins et al, 2012). Moreover, the relatively recently acquired ability to collect wholegenome expression profiles and deep DNA sequence information from small amounts of tumor biopsy material has provided an opportunity to greatly expand the use of molecular profiling in guiding drug development and treatment decisions.…”
mentioning
confidence: 99%
“…The lack of good comparative effectiveness evidence for oncology drugs, particularly for off-label uses, has been well described and sorely lamented. 21,22 But a complex legislative and regulatory framework shields cancer drugs from potential strategies that would apply a standard of evidence based on comparative effectiveness, as opposed to efficacy versus placebo, as a mechanism to restrict coverage. 23 For Medicare Part B injectable drugs, federal law requires Medicare to cover any drug used in an "anticancer chemotherapeutic regimen," as long as the use is "for a medically accepted indication."…”
Section: Coverage Of and Payment For Oncology Drugsmentioning
confidence: 99%
“…2 We also appreciate the extent of their previous research in related areas. Their comments highlight the need for better evidence of the effectiveness of oncology drugs and a better means for using the best available evidence to inform coverage decisions.…”
mentioning
confidence: 96%
“…Patients in the palliative care intervention arm also had an improved quality of life, less chemotherapy at the end of life, and earlier referral to hospice care. In his editorial on the study by Greer et al, 2 Earle, who is a medical oncologist, cited the poor competence of oncologists in addressing palliative care/end-of life discussions and suggested that palliative care specialists be the primary discussants of difficult issues rather than medical oncologists. 3 The American Society of Clinical Oncology has issued provisional guidelines that recommend that "combined standard oncology care and palliative care should be considered early in the course of illness for any patient with metastatic cancer."…”
mentioning
confidence: 97%
See 1 more Smart Citation